A case of zolpidem dependence with extremely high daily doses. (1st May 2019) - Bajaj, Vikrant; Kalra, Ishat; Bajaj, Arushi; Sharma, Devasheesh; Kumar, Rohit
Abstract: The human population has been witnessing an increase in the number of diseases which are a consequence of progressively increasing physical and mental stress. Insomnia is one such condition whose prevalence is rising all over the world. Apart from the conventional behavioral interventions and use of benzodiazepines, the use of non‐benzodiazepine drugs has seen a surge in recent times. The various adverse effects associated with benzodiazepines, dependence potential being one of them, led to an ever increasing use of non‐benzodiazepine sedatives like zolpidem and zopiclone all over the world. But with their continuous and ever increasing use, it is seen that even these drugs carry dependence potential. Numerous cases of zolpidem abuse have been reported in literature until now. Here, we are presenting the case of a zolpidem‐dependent patient who consumed it in quantities of 2400 mg/day, a quantity not reported anywhere in literature and around 240 times more than its usual prescribed daily dosage.